Best Practices for Teachers in Stimulating the Language Development of Deaf Children through Visual Media - Susianti; Retno Risti Darmawanti; Sefriyanti (Universitas PGRI Madiun, 2026)
Deaf children experience language development challenges due to hearing limitations that affect their ability to receive and produce language. This condition requires learning strategies tailored to their learning characteristics. This study aims to describe teachers' best practices in stimulating the language development of children with hearing impairments through the use of visual media at Amartya Kindergarten in Bantul. This study used a qualitative descriptive approach. The subjects consisted of the principal, class teachers, and three children with hearing impairments. Data were collected through observation and interviews. Data validity was verified through source triangulation, while data analysis included data reduction, data presentation, and conclusion drawing. The results showed that the best practices implemented by teachers included identifying children's language needs, using visual media such as sign language learning videos, picture cards, flashcards, and puzzles, and encouraging communication in daily activities using sign language. These practices help children understand vocabulary and sign language more easily and encourage active involvement in learning. These findings indicate that using visual media tailored to the visual learning characteristics of deaf children is a learning practice that supports language development in early childhood education.